Atypical presentations of cutaneous tuberculosis: A series of four cases - Swetha Chowdary Atluri; Santhosh Kumar Arepalli; Divya Manchala; Vamshi Chetan Talari; S Haritha (Wolters Kluwer Medknow Publications, 2023)
Tuberculosis (TB), caused by Mycobacterium TB, is one of the leading causes of major illness and death worldwide. Although cutaneous TB constitutes a small proportion of extrapulmonary TB burden, awareness regarding varied clinical presentations is necessary as early diagnosis and treatment are keys to reduce the morbidity of the disease. Here, we present a series of four rare cases of cutaneous TB presenting as vulval elephantiasis, Poncet's disease, disseminated TB, and anterior chest wall TB. These cases posed diagnostic difficulty due to unusual presentations. However, all the cases responded well to antitubercular treatment.